Metafizyczne określenia w orzeczeniach soborów starożytnego Kościoła – przyczynek do dyskusji nad duchem i literą dogmatu - Kosmulska, Bogna (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2013)
In my article I compare two different approaches to a problem of Christian dogma in the shape of classical metaphysical language of ancient Church councils: 1) the proposition of Vladimir Solovyov to rethink metaphysics but to treat it as a still legitimate expression of the very centre of Christianity, and 2) that of Bernhard Welte to rethink Christianity without classical metaphysics. By comparing not only plain theses of both authors but also their historical context I discuss a paradoxical possibility of agreeing with Solovyov (and not with Welte) in our time of «a long farewell to metaphysics» by an attempt to make use of contemporary knowledge of ancient Christianity. This perspective gives a possibility to rethink also present-day Christianity without loosing the continuity of Church tradition which by the letter is always trying – just like nowadays – to find the spirit of dogma.